A Thought on Applicability of Sun Tzu’s Strategy on Marketing Strategy - Fenny Widyani Hartanto; Maria Yoshephine Dwi Hayu Agustini (Journal of Management and Business Environment (JMBE), 2020)
Sun Tzu’s strategy is actually an art of war used by Chinese military under Sun Tzu to win the war. Its application has been widespread beyond the military strategy. It has also been adopted for business strategy. This manuscript is to examine applicability of Sun Tzu’s strategy on marketing. In particularly it examines if Sun Tzu’s strategy can be applied as marketing strategy. Review manuscripts in related topics and a case study on a company are the method for the examination. The result indicates that Sun Tzu’s strategy is applicable in marketing and can be related with specific marketing terms.